Optimal Pretreatment of Eucalyptus Globulus by Hydrothermolysis and Alkaline Extraction for Microbial Production of Ethanol and Xylitol - Yanez-Sanchez, M (2013)
Fractionation of Eucalyptus globulus wood chips is mandatory for developing a biorefinery process. In order to achieve this, products released from hydrothermolysis pretreatment were studied within the severity (log R 0) range 3.3-4.5. The highest solubilized xylose yield was 56% (DWB) at log R0 3.9. Values higher than log R0 4.1 have led to high xylose dehydration rates. Detoxification steps applied to the liquor removed acetic acid (55%), furfural (94%), and hydroxymethylfurfural (HMF) (31%). Fermentation of liquor with Candida guilliermondii resulted in a xylitol yield of 0.37 g of xylitol produced per gram of xylose consumed (equivalent to 71% of the control with pure xylose). Pulp-1 (from hydrothermolysis pretreatment) was further pretreated with NaOH for lignin removal (obtaining Pulp-2). Cellulose composition in Pulp-1 and Pulp-2 remains almost unaltered; lignin content in Pulp-2 was 50% lower than in Pulp-1. Simultaneous saccharification and fermentation (SSF) experiments for both pulps reached similar ethanol yields of 0.76 and 0.70 g of ethanol produced per gram of ethanol potentially produced from wood, respectively. Recovery of hemicellulose at the beginning of the process is a key step for getting pulps with high cellulose composition available for developing a biorefinery process of E. globulus. © 2013 American Chemical Society.